Preparation method and application of in-situ carbon-coated molybdenum phosphide

Through the preparation method of in-situ carbon coated molybdenum phosphide, the problems of poor stability of molybdenum phosphide and uneven coating of carbon materials are solved, and a catalyst material with high stability and high electrocatalytic properties are achieved.

CN119843316APending Publication Date: 2025-04-18WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510048985.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, molybdenum phosphide is prone to oxidation or corrosion during long-term electrochemical work, resulting in poor stability. The existing preparation methods are complex and have a long period, making it difficult to uniformly coat the carbon material on the surface of molybdenum phosphide.

Method used

Through the preparation method of in-situ carbon coated molybdenum phosphide, using molybdenum carbide as a frame and template, through the phosphating reaction, the C atoms in molybdenum carbide are replaced and deposited on the surface of molybdenum phosphide to form a tight carbon layer. The method includes steps such as drying, mixing with the phosphorus source in a certain proportion, heating and phosphating, pickling and drying.

Benefits of technology

The uniform coating of the carbon layer is achieved, the chemical stability and electrocatalytic properties of molybdenum phosphide are improved, and the uneven existence and loose fall of carbon materials are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843316A_ABST
    Figure CN119843316A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst preparation, and particularly discloses a method for preparing carbon-coated molybdenum phosphide, which comprises the following steps: by using molybdenum carbide as a framework and a template, replacing carbon atoms in the molybdenum carbide through phosphorization reaction to obtain the molybdenum phosphide. The in-situ replacement mode belongs to a non-destructive replacement reaction, the original morphology and structure of molybdenum carbide can be kept, and meanwhile, part of the replaced carbon is deposited on the surface of molybdenum phosphide to form an in-situ carbon layer which is tightly coated on the surface of molybdenum phosphide. According to the in-situ replacement method provided by the invention, the preparation difficulty of the carbon-coated molybdenum phosphide can be greatly reduced, and the preparation which is short in period, simple, convenient and easy to industrialize is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst material preparation technology, and specifically relates to a method for preparing in-situ carbon-coated molybdenum phosphide by phosphating molybdenum carbide and application thereof. Background Art

[0002] Hydrogen is gradually playing an important role in the energy economy. At the same time, water electrolysis of hydrogen, as an ideal energy carrier for renewable energy, can promote the re-conversion of surplus electricity from new energy sources (such as solar energy and wind energy). Therefore, in order to achieve large-scale hydrogen production and efficient utilization of new energy, it is urgent to design excellent hydrogen evolution reaction (HER) electrocatalysts to accelerate the water splitting process. Considering the high price and scarcity of precious metal catalysts, which hinder their further large-scale commercial application, it is urgent to develop efficient and stable non-precious metal catalysts to meet production needs. Molybdenum phosphide is considered to be a promising catalyst due to its natural abundance and high efficiency and activity, but it is easily oxidized or corroded in long-term electrochemical work, resulting in its gradual failure. Therefore, it is necessary to modify the surface of molybdenum phosphide to improve its stability.

[0003] In terms of preparation methods, the molybdenum source and the carbon-containing precursor are usually stirred and mixed for a long time, dried, and finally phosphated. The existing methods have many preparation processes and long cycles, and the obtained carbon materials are difficult to be evenly coated on the surface of molybdenum phosphide, which greatly limits the design and research of stable molybdenum phosphide. Therefore, further exploring the preparation process of in-situ carbon-coated molybdenum phosphide with high efficiency, low cost and easy operation has important research and application significance. Summary of the invention

[0004] In order to solve the defects existing in the prior art, the present invention discloses a method for preparing in-situ carbon-coated molybdenum phosphide, and its technical scheme is as follows:

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] 1. A method for preparing in-situ carbon-coated molybdenum phosphide, characterized in that it comprises the following steps:

[0007] Step 1: First, dry the molybdenum carbide;

[0008] Step 2: weighing molybdenum carbide and phosphorus source according to a certain mass ratio;

[0009] Step 3: placing molybdenum carbide and a phosphorus source in an alumina crucible respectively, and placing the phosphorus source at an upstream position of the quartz tube;

[0010] Step 4: Continue to introduce inert gases such as Ar and N2 into the quartz tube, exhaust the air in the tube, and keep the flow rate unchanged during the subsequent heating reaction;

[0011] Step 5: heating to 850-950°C at a heating rate of 5-10°C / min;

[0012] Step 6: After reaching the temperature, the reaction is kept warm for 3 to 6 hours;

[0013] Step 7: After the reaction is completed, wait for the furnace temperature to cool to room temperature and take out the reactants;

[0014] Step 8: After acid washing, the reactant is filtered or centrifuged;

[0015] Step 9: Dry the product to obtain in-situ carbon-coated molybdenum phosphide.

[0016] Preferably, the molybdenum carbide and the phosphorus source are weighed in a certain amount, and the mass ratio of molybdenum carbide to phosphorus source is 1:20 to 1:50. The phosphorus source decomposes at high temperature, and a part of it will be taken out of the quartz tube by the protective gas, causing inevitable loss. In order to ensure sufficient reaction, an excess of phosphorus source is required.

[0017] Preferably, the morphology of the molybdenum carbide powder includes but is not limited to flake, ribbon, rod, etc.

[0018] Preferably, the drying step can be performed by oven drying or freeze drying.

[0019] Preferably, the phosphorus source includes but is not limited to sodium hypophosphite, sodium hypophosphite, and red phosphorus.

[0020] Preferably, the crucible is an alumina crucible, which can withstand a high temperature below 1800°C.

[0021] Preferably, the protective atmosphere is an inert atmosphere, argon or nitrogen;

[0022] Preferably, the flow rate of the protective atmosphere is 50-100 mL / min, which maintains an inert environment while reducing the loss of phosphorus source caused by gas discharge;

[0023] Preferably, the speed selected for centrifugation is 3000-5000 rpm. The obtained carbon-coated molybdenum phosphide powder is light in weight, and it is difficult to completely separate the molybdenum phosphide powder from the solution by centrifugation at a low speed.

[0024] Preferably, the transition metal boride is prepared and heated to 850-950° C. Molybdenum carbide has good thermal stability and a high melting point. Low temperature may easily lead to incomplete phosphating reaction and the presence of some molybdenum carbide precursors.

[0025] Preferably, the temperature is kept at 3 to 6 hours. Phosphating molybdenum carbide is a reaction process from outside to inside, and a certain amount of time is required for the phosphating reaction to be complete.

[0026] The present invention also discloses an in-situ carbon-coated molybdenum phosphide, which is obtained by the above-mentioned preparation method of in-situ carbon-coated molybdenum phosphide. The in-situ carbon-coated molybdenum phosphide is a core-shell structure coated with a high-crystallinity carbon material; it is a catalyst material with a hexagonal crystal structure with orderly atomic arrangement and clear stoichiometry, and has high electrocatalytic performance and chemical stability.

[0027] The present invention also discloses a catalyst material, which is characterized in that the material comprises the above-mentioned in-situ carbon-coated molybdenum phosphide.

[0028] The invention also discloses a hydrogen evolution reaction electrocatalyst, which is characterized by comprising the above catalyst material.

[0029] Beneficial Effects

[0030] 1) The present invention proposes that by utilizing molybdenum carbide for one-step phosphating, the reaction steps can be greatly reduced, and carbon-coated molybdenum phosphide can be prepared in a simple and easy one-step manner.

[0031] 2) The in-situ replacement method is a non-destructive replacement reaction, which can maintain the original morphology and structure of molybdenum carbide. Therefore, by selecting molybdenum carbide precursors with different morphologies, carbon-coated molybdenum phosphide catalysts with different structures and morphologies can be obtained.

[0032] 3) During the preparation process of the carbon coating of the present invention, the carbon replaced in the lattice is in-situ deposited on the surface of the molybdenum phosphide, so as to obtain a coating layer with uniform thickness and avoid the uneven presence of carbon materials.

[0033] 4) During the preparation process of the carbon coating of the present invention, the carbon layer is tightly coated on the surface of molybdenum phosphide in situ, so the carbon layer has a strong bonding ability with molybdenum phosphide. This structure makes the catalyst have a significant anti-corrosion effect in long-term electrochemical work and avoids the loosening and falling of carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 XRD of MoP prepared in Example 1 of the present invention;

[0035] Figure 2 TEM of MoP prepared in Example 1 of the present invention;

[0036] Figure 3 This is the SEM of the precursor MoC in Example 2 of the present invention;

[0037] Figure 4 XRD of MoP prepared in Example 2 of the present invention;

[0038] Figure 5 This is the SEM of MoP prepared in Example 2 of the present invention;

[0039] Figure 6XRD of MoP prepared in Example 3 of the present invention;

[0040] Figure 7 This is the SEM of MoP prepared in Example 3 of the present invention;

[0041] Figure 8 This is the SEM of the precursor MoC in Example 4 of the present invention;

[0042] Fig. 9 XRD of MoP prepared in Example 4 of the present invention;

[0043] Fig.10 This is the SEM of MoP prepared in Example 4 of the present invention;

[0044] Fig.11 Schematic diagram of the structure of carbon-coated molybdenum phosphide. DETAILED DESCRIPTION

[0045] The present invention is further described in detail with reference to specific embodiments. Wherein, the methods are conventional methods unless otherwise specified. The raw materials can be obtained from public commercial channels unless otherwise specified. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0046] Example 1

[0047] 1) The dried molybdenum carbide nanosheets and sodium hypophosphite are respectively placed in an alumina crucible at a mass ratio of 1:30;

[0048] 2) Place the crucible in a tube furnace, place the phosphorus source upstream of the quartz tube, and evacuate the air in the tube at an argon flow rate of 50 mL / min;

[0049] 3) Heat to 850°C in an argon atmosphere and keep the temperature for 3 hours, and take out the reaction product after the furnace cools to room temperature;

[0050] 4) The obtained reaction product was added to a 1M HCl solution and washed and stirred for 1 hour, and then repeatedly washed with deionized water for 3 to 5 times. After suction filtration, the product was placed in a freeze dryer overnight to obtain carbon-coated molybdenum phosphide nanosheets.

[0051] The samples were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (TEM). Figure 1 and Figure 2 The XRD results show that the diffraction peak of the obtained product is consistent with the standard card NO.65-6487 of MoP. From the TEM image, it can be seen that there is an obvious carbon layer on the surface of MoP, which is significantly different from the general carbon-coated molybdenum phosphide material. The MoP is evenly and tightly coated with the surface carbon layer.

[0052] Example 2

[0053] 1) The dried molybdenum carbide nanosheets and sodium hypophosphite are respectively placed in an alumina crucible at a mass ratio of 1:30;

[0054] 2) Place the crucible in a tube furnace, place the phosphorus source upstream of the quartz tube, and evacuate the air in the tube at an argon flow rate of 80 mL / min;

[0055] 3) Heat to 750°C in an argon atmosphere and keep warm for 1 hour, and take out the reaction product after the furnace cools to room temperature;

[0056] 4) The obtained reaction product was added to a 1M HCl solution and washed and stirred for 1 hour, then repeatedly washed with deionized water for 3 to 5 times, filtered, and then placed in a freeze dryer overnight.

[0057] The obtained samples were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Figure 3 The results of phosphating treatment are shown in Figure 4 and Figure 5 The XRD results show that the sample still has some MoC phase, corresponding to standard card NO.65-6664. The SEM image also shows that the original nanosheets are still preserved.

[0058] Example 3

[0059] 1) The dried molybdenum carbide nanosheets and sodium hypophosphite are respectively placed in an alumina crucible at a mass ratio of 1:30;

[0060] 2) Place the crucible in a tube furnace, place the phosphorus source upstream of the quartz tube, and evacuate the air in the tube at an argon flow rate of 80 mL / min;

[0061] 3) Heat to 1000°C in an argon atmosphere and keep the temperature for 4 hours, and take out the reaction product after the furnace cools to room temperature;

[0062] 4) The obtained reaction product was added to a 0.5M HCl solution and washed and stirred for 3 hours, then repeatedly washed with deionized water for 3 to 5 times, filtered, and then placed in a freeze dryer overnight.

[0063] The samples were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Figure 6 and Figure 7 The XRD results show that the diffraction peak of the obtained product is consistent with the standard card NO.65-6487 of MoP. From the SEM image, it can be seen that the morphology of MoP is melted, resulting in structural collapse.

[0064] Example 4

[0065] 1) The dried molybdenum carbide nanobelts and sodium hypophosphite are respectively placed in an alumina crucible at a mass ratio of 1:40;

[0066] 2) Place the crucible in a tube furnace, place the phosphorus source upstream of the quartz tube, and evacuate the air in the tube at an argon flow rate of 80 mL / min;

[0067] 3) Heat to 800°C in an argon atmosphere and keep the temperature for 3 hours, and take out the reaction product after the furnace cools to room temperature;

[0068] 4) The obtained reaction product was added to a 0.5M HCl solution and washed and stirred for 3 hours, then repeatedly washed with deionized water for 3 to 5 times, filtered, and then placed in a freeze dryer overnight.

[0069] The obtained samples were analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Figure 8 The results of phosphating treatment are shown in Fig. 9 and Fig.10 The XRD results show that the diffraction peak of the obtained product is consistent with the standard card NO.65-6487 of MoP. From the SEM image, it can be seen that the morphology of MoP is consistent with that of the precursor MoC, and it is still a nanobelt morphology.

[0070] The present invention provides a method for preparing in-situ carbon-coated molybdenum phosphide, using molybdenum carbide as a framework and template, and through a phosphating reaction, C atoms in molybdenum carbide are replaced to obtain molybdenum phosphide, and a part of the replaced C atoms are deposited on the surface of molybdenum phosphide to form an in-situ carbon layer. The in-situ replacement method belongs to a non-destructive replacement reaction, which can maintain the original morphology and structure of molybdenum carbide. The thickness of the formed carbon layer is usually 2 to 3 nm, with high crystallinity, and is tightly coated on the surface of molybdenum phosphide to form a protective layer of core-shell structure. The material is a catalyst material with an orderly atomic arrangement and a hexagonal crystal structure with clear stoichiometry, and has high electrocatalytic performance and chemical stability.

[0071] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing in-situ carbon-coated molybdenum phosphide, characterized in that: The steps include: Step 1: First, dry the molybdenum carbide; Step 2: weighing molybdenum carbide and phosphorus source according to a certain mass ratio; Step 3: placing molybdenum carbide and a phosphorus source in an alumina crucible respectively, and placing the phosphorus source at an upstream position of the quartz tube; Step 4: Pass an inert atmosphere such as Ar or N2 into the quartz tube at a flow rate of 50-100 mL / min; Step 5: heating to 850-950°C at a heating rate of 5-10°C / min; Step 6: After reaching the temperature, the reaction is kept warm for 3 to 6 hours; Step 7: After the reaction is completed, wait for the furnace temperature to cool to room temperature and take out the reactants; Step 8: After acid washing, the reactant is filtered or centrifuged; Step 9: Dry the product to obtain in-situ carbon-coated molybdenum phosphide.

2. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The morphology of the molybdenum carbide powder includes but is not limited to flake, ribbon, and rod.

3. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The phosphorus source includes but is not limited to sodium hypophosphite, sodium hypophosphite, and red phosphorus.

4. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The mass ratio of the molybdenum carbide to the phosphorus source is 1:20 to 1:

50.

5. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The process of pickling and drying includes washing with dilute hydrochloric acid, then washing two to three times with deionized water, and then filtering or centrifuging to dry.

6. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The acid washing method is: transferring the reaction product into hydrochloric acid with a concentration of 0.5 to 2 M and stirring for 0.5 to 3 hours.

7. The method for preparing in-situ carbon-coated molybdenum phosphide according to claim 1, characterized in that: The speed selected for centrifugation is 500-2000 rpm.

8. In-situ carbon-coated molybdenum phosphide, obtained by the preparation method of in-situ carbon-coated molybdenum phosphide according to any one of claims 1 to 7, wherein the in-situ carbon-coated molybdenum phosphide is a core-shell structure coated with a high-crystallinity carbon material; it is a catalyst material with a hexagonal crystal structure with orderly atomic arrangement and clear stoichiometry, and has high electrocatalytic performance and chemical stability.

9. A catalyst material, characterized by: The material comprises the in-situ carbon-coated molybdenum phosphide as claimed in claim 8.

10. A hydrogen evolution reaction electrocatalyst, characterized by: Comprising the catalyst material according to claim 9.

Citation Information

Cited By

  • Preparation method and application of Mo2C / Mo3P heterojunction catalyst with core-shell structure

    CN120666382A